2003
DOI: 10.1080/718591716
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of various tests for bacterial vaginosis in predicting preterm birth—a systematic review

Abstract: Objective To determine the accuracy with which various types of tests for bacterial vaginosis predict spontaneous preterm birth in pregnant women. Data sources Studies were identified without language restrictions through nine different databases, and manual searching of bibliographies of known primary and review articles. Study selection and data extraction There are four different bacterial vaginosis testing methods: Gram staining tests using either Nugent's or Spiegel's criteria, and gas liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Bacterial vaginosis diagnosed according to Nugent's criteria provided an LR+ of 1.6 (20) (number of screen‐positive PTD >100), and vaginal carriage of group B streptococci was not associated with PTD (21) (number of screen‐positive PTD 50–100). Based on one small study, the finding of Ureaplasma urealyticum in amniotic fluid had an LR+ of 10.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial vaginosis diagnosed according to Nugent's criteria provided an LR+ of 1.6 (20) (number of screen‐positive PTD >100), and vaginal carriage of group B streptococci was not associated with PTD (21) (number of screen‐positive PTD 50–100). Based on one small study, the finding of Ureaplasma urealyticum in amniotic fluid had an LR+ of 10.…”
Section: Resultsmentioning
confidence: 99%
“…A Swedish study found comparable results (LR+ of 7, SENS 35%, and FP 5%) for predicting PTD before 34 weeks (7). The association of BV with PTD is well documented, and the pooled LR+ estimate was 1.3 (1.0–1.6) in a metaanalysis on 575 subjects using Spiegel's criteria (8).…”
Section: Infection and Inflammationmentioning
confidence: 99%
“…Another recently published meta‐analysis studied the accuracy of different tests for BV when predicting preterm birth (36). Studies testing asymptomatic women in the second trimester showed that clinical criteria had a likelihood ratio (LR) of 0.98 (95% CI 0.59 to 1.6) and an LR‐ of 1.00 (0.93 to 1.1), Gram‐staining (Nugent's criteria) had an LR+ of 1.6 (1.4 to 1.9) and an LR‐ of 0.9 (0.8 to 0.9), and Gram‐staining (Spiegel's criteria) had an LR+ of 2.4 (1.4 to 4.9) and an LR‐ of 0.81 (0.64 to 1.0).…”
Section: Bv During Pregnancymentioning
confidence: 99%